Pengembangan Media Pembelajaran Holografis (Studi Kasus : Bab Indera Pendengaran Manusia) - Abdul Azis; Wibisono Sukmo Wardhono; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Humans have the sense of hearing that is the function of the ear for balance and to capture the source of sound from outside. There are four parts to the discussion of material on the sense of hearing, namely the outer ear, middle ear, inner ear and the mechanism of the listening process. Teaching materials given by teachers to students today use the media explanation from Student Worksheets (LKS), blackboards, which can make students feel inclined to get bored, lazy to listen, feel sleepy and there is less attention. All means of learning activities are expected to be able to support students to understand clearly what is conveyed by the teacher or instructor in order to foster a desire to study more actively with proportional learning media (Daryanto, 2016). Holographic is a two dimensional object that has been documented and subsequently reappeared with changes in the location and direction of the gaze until it appears as though three dimensions (Kurniawan, 2017). This application will be implemented on an Android smartphone screen using prism acrylic projection media and can then be displayed in three dimensions and can be viewed in 3600. The method used to assess an item that is tested to the user and later will be given input by the user when finished operating the system, that is which is called usability testing (Lodhi, 2010). Hearing sensory learning applications ranging from learnability, effeciency, memorability, error and satisfaction. It has been tested to 13 reporters after operating the application, then got the results of 13 reporters namely: strongly agree = 62, agree = 38, neutral = 32 and disagree = 0. Furthermore, of the total answers, then the usability percentage is 82.3% and qualifications are categorized good or successful when seen in a quantitative table according to Arikunto..